2008
DOI: 10.1097/sla.0b013e31818990d1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Perioperative Hyperglycemia and Postoperative Infections in Patients Who Undergo General and Vascular Surgery

Abstract: The increased risk of POI and length of hospitalization posed by postoperative hyperglycemia is independent of diabetic status and needs further evaluation to assess for possible benefits of postoperative glycemic control in patients who have undergone general surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
197
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(205 citation statements)
references
References 28 publications
3
197
1
4
Order By: Relevance
“…There are currently several debates regarding the benefits of strict glucose control in less critically ill patients undergoing elective surgery as opposed to critically ill (medical) patients12, 13, 14, 15, 16, 17, 18 (Table 2). Although the recommended target BG is 140–180 mg/dL for most ICU patients,27 a recent meta‐analysis23 comparing the efficacy between an intensive and a conventional protocol in patients undergoing surgery showed a significant benefit for the intensive protocol in reducing SSI.…”
Section: Indication For Intensive Protocol In Critically Ill Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are currently several debates regarding the benefits of strict glucose control in less critically ill patients undergoing elective surgery as opposed to critically ill (medical) patients12, 13, 14, 15, 16, 17, 18 (Table 2). Although the recommended target BG is 140–180 mg/dL for most ICU patients,27 a recent meta‐analysis23 comparing the efficacy between an intensive and a conventional protocol in patients undergoing surgery showed a significant benefit for the intensive protocol in reducing SSI.…”
Section: Indication For Intensive Protocol In Critically Ill Patientsmentioning
confidence: 99%
“…Bivariate analysis revealed that compared with patients with a first postoperative BG ≤110 mg/dL, the likelihood of acquiring an SSI increased progressively for patients with higher BG (OR 3.61 for 111–140 mg/dL; OR 6.26 for 141–180 mg/dL; OR 5.92 for 181–220 mg/dL; and OR 12.13 for >220 mg/dL). In a logistic model, Ramos et al 15. reported that every 40 mg/dL increase from normoglycemia (<110 mg/dL) led to a 30% increased risk of infection.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] However, the risks of unrecognized hyperglycemia (in patients not known to have diabetes) prior to surgical operations remain unclear. Although Ramos et al have investigated associations between post-operative hyperglycemia and post-operative complications, 10 we were interested in using pre-operative blood glucose as a marker for post-operative complications in patients not known to have diabetes. These patients would not be expected to have HbA1c levels, making blood glucose screening a potentially useful tool to screen for post-operative risks and act as a gateway to connect these patients to short-and long-term monitoring and management of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%